RANCANG BANGUN SISTEM PENGONTROLAN PERANGKAT LISTRIK PADA RUANGAN DENGAN SENSOR PIR MENGGUNAKAN ARDUINO UNO R3 - Eko Kurniawanto Putra, S.Pd; Akmal (ITP Press, 2016)
To solve a problem such as excessive use of electrical devices. Control of electrical energy can be done by designing a tool control system. Controlling can be done by controlling electrical equipment in a room. To add to the convenience of using a room takes a variety of electrical equipment. Most of the users forget to turn off electric appliances when finished using the room, so it will affect the excessive use of electrical energy. Therefore we need a control that can be set on the use of electrical energy in the room. Required a system that could control the use of such equipment. One of the control system can use a PIR motion sensor that detects motion of an object that is in front of the sensor within a certain range. In order to function properly control required position of the sensor. So it can detect any object in the room from any angle the object is located. Retrieval of data from the sensor's delay for the best sensor placement so that it can detect all objects in the room. After looking at the data obtained by experiments that have been done. Then the most ideal position in setting the sensor in the testing of this tool is the left side of the room using two sensors. It is based on the delay obtained from this position at least from another position that is 0.970 seconds.